Audit Tenure, Audit Committee, Audit Fee, Audit Delay: Effect on Audit Quality - Anapi Rahman; Artie Arditha Rachman; Irawan Irawan (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the simultaneous effect of audit tenure, audit committee, audit fee, and audit delay on audit quality in manufacturing companies within the basic materials sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. Methodology/approach: The research uses a quantitative approach with secondary data obtained from annual reports of basic materials sector companies listed on the IDX for the years 2020–2023. Sampling was conducted using purposive sampling, and analysis was performed using logistic regression through IBM SPSS 26 software. Results/findings: The results indicate that audit tenure, audit committee, audit fee, and audit delay simultaneously affect audit quality. The Nagelkerke R Square value of 0.590 shows that these variables explain 59% of the variation in audit quality. The model also has an overall prediction accuracy of 88%. Conclusions: The research concludes that audit tenure, audit committee, audit fee, and audit delay simultaneously have a significant effect on audit quality in basic materials manufacturing companies listed on the IDX for the 2020–2023 period. Limitations: This study is limited to companies in the basic materials sector listed on the IDX during 2020–2023, which may restrict the generalizability of the findings to other sectors. Contribution: The findings provide insights for companies, auditors, and regulators on the importance of monitoring mechanisms such as audit tenure, audit committee, audit fees, and audit delay in ensuring audit quality, particularly in the basic materials sector.